Probing a one-loop quantum-corrected Schwarzschild spacetime with precessing and periodic motion - Ze-Lin Wei; Jing Zhang; Yi Xie; Pei-Lin Yin (European Physical Journal C: Particles and Fields)
Abstract We investigate the bound orbits of a test timelike particle around the Schwarzschild spacetime with one-loop quantum correction in this work. After obtaining the marginally bound orbit and innermost stable circular orbit numerically, we find that both of their radii decrease with the rescaled quantum-corrected parameter $$λ .$$ λ . Then, we scrutinize the precessing orbits and work out the resulting relativistic periastron advance, which descends with the increment of the one-loop long-distance quantum-corrected effect and could depart from the one in the Schwarzschild spacetime slightly. Based on that, we try to constrain the quantum-corrected effect around the Sgr A* by employing the observation of GRAVITY on S2 star and find a preliminary bound on it. Moreover, we examine the periodic orbits in this spacetime and find that they lay out a distinct pattern from the one in the Schwarzschild spacetime due to the quantum-corrected parameter $$λ ,$$ λ , which may give an insight into the quantum effect of the spacetime in the strong gravitational field.